Effect of Ammonia on the Synthesis of NMC541 Cathode Materials with the Sol-Gel Method - Yustinus Purwamargapratala; Jihan Fakhriyah Safitri; Eduardus Budi Nursanto; Heri Jodi; Evvy Kartini; Anne Zulfia (BRIN Publishing (Penerbit BRIN), 2023)
The research studied about the effect of ammonia on the synthesis of lithium-ion battery cathode materials LiNi0.5Mn0.4Co0.1O2 (NMC541) through a sol-gel method by modifying the mole ratio of ammonia to metal forming ratios (0.5; 1.0; 1.5; and 2.0). The precipitation formed at pH 11 and at temperature of 80oC. Characterization was carried out on samples resulting from pyrolysis (pyrolysis result), with calcination for once and twice at 850oC for 3 hours, X-ray diffraction pattern characterization, morphological characterization using scanning electron microscope (SEM), and conductivity characterization using an impedance capacitance conductance (LCR) meter. The result of the synthesis is in the form of spherical particles. The addition of ammonia affected the particle size distribution and stoichiometry of the metal forming NMC541, eventhough it was not significant. The ammonia to metal ratio of 1.5 (Sample N1.5-K) resulted in the distribution with the optimum particle homogeneity. The morphology of the pyrolysis and 3 hours-850oC calcined samples was dominated by spherical particles and agglomeration. Particle growth in the material is affected by heat treatment time. Samples with ammonia to metal ratio of 2.0 (N2.0-K) have the closest stoichiometry to NMC541. The total conductivity of the sample at a measurement frequency of 42Hz-1MHz is in the value range of 10-7–10-5 S.cm-1. The particle size is also affected by the calcination temperature. The effect of using ammonia in the synthesis process is not directly related to the electrical properties. However, it is related to the purity of NMC541. Samples of N1.5-K pyrolyzed result and samples of N1.0-K (3 hour 850 oC calcined) have optimum conductivity values. Agglomeration as a calcination effect lowers the conductivity value. The addition of 3 hours of calcination time does not significantly increase the conductivity value